Design of Google Sites-Based Learning Media Using the Group Investigation Model on Convection Concepts and Its Effect on Students’ Learning Outcomes - Santosa, Veronika Nelvasia Devi; Haryani, Fairusy Fitria (KnE Social Sciences, 2025)
This paper aims to design learning media using Google Sites by applying the group investigation (GI) cooperative learning model on convection material for students and to determine the effect of Google Sites-based learning media on improving student learning outcomes. The method used is a literature study that reviews several journals. The results concluded that: 1) Google Sites learning media that applies the GI cooperative learning model are designed by the flow of activities used for students. 2) With an increase in the average score of students from pretest to posttest, the use of Google Sites as a learning media seems to have a good effect on improving student learning outcomes.